(untitled) (Bangladesh Journal of Botany, 2019)
The present investigation was conducted to elucidate the interrelationship among various yield and yield contributing traits. Among the traits plant height, days to 50% flowering, days to maturity, filled grain per panicle and spikelet sterility showed high genotypic variance. Effective tillers per hill, filled grain per panicle, spikelet sterility had high genotypic coefficient of variation with high heritability and high genetic advance per cent of mean. Effective tillers per hill, panicle length, filled grain per panicle and 1000-grain weight exhibited significant positive association with grain yield. Path coefficient analysis also revealed that plant height, effective tillers per hill, panicle length and 1000-grain weight had higher direct effect on rice yield (t/ha). Days to 50% flowering, days to maturity and spikelet sterility possessed moderate to low negative direct effect on rice yield. All together with the genetic variability, correlation and path analysis revealed that plant height, effective tillers per hill, panicle length, filled grain per panicle and 1000-grain weight were the most important yield component in rice hybrids.